2019
DOI: 10.3389/fpsyg.2019.02147
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality and Measurement Invariance of the Italian Version of the EORTC QLQ-C30 in Postoperative Lung Cancer Patients

Abstract: BackgroundThis study aims to validate and evaluate the psychometric properties and measurement invariance of the Italian version of the European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire-Core 30 (QLQ-C30), which is a measure of quality of life (QoL) for lung cancer patients after surgery.MethodsA total of 167 lung cancer patients completed the Italian version of the EORTC QLQ-C30 questionnaire at 30 days after they received a lobectomy. The factor structure of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
0
11
2
Order By: Relevance
“…This is in line with Costa et al [ 9 ] who found little bias in the comparison of patients with various primary cancers. While a previous study by Marzorati et al [ 8 ] found MI with regard to sex, we only found marginal differences on item level. Also, findings from a study by King-Kallimanis et al [ 7 ] and Marzorati et al [ 8 ] indicated some measurement bias based on age; however, in those studies and in our study effect sizes of the changes in the item’s associated factor means were small to medium.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This is in line with Costa et al [ 9 ] who found little bias in the comparison of patients with various primary cancers. While a previous study by Marzorati et al [ 8 ] found MI with regard to sex, we only found marginal differences on item level. Also, findings from a study by King-Kallimanis et al [ 7 ] and Marzorati et al [ 8 ] indicated some measurement bias based on age; however, in those studies and in our study effect sizes of the changes in the item’s associated factor means were small to medium.…”
Section: Discussioncontrasting
confidence: 99%
“…While a previous study by Marzorati et al [ 8 ] found MI with regard to sex, we only found marginal differences on item level. Also, findings from a study by King-Kallimanis et al [ 7 ] and Marzorati et al [ 8 ] indicated some measurement bias based on age; however, in those studies and in our study effect sizes of the changes in the item’s associated factor means were small to medium. Other studies found measurement bias with regard to change over time (patients pre- and post-cancer treatment) [ 4 , 5 ], while we, with regard to time since diagnosis, and Scott et al 2009 [ 6 ] with regard to disease trajectory, did not.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The EORTC QLQ-C30 is the most commonly used tool for measuring QoL in lung cancer patients. Several studies reported good psychometric properties, demonstrating an excellent convergent and discriminant validity with the Functional Assessment of Cancer Therapy—General (FACT-G) questionnaire and good reliability for all domains (Cronbach's α higher than 0.70) (Jocham et al, 2009 ; Iravani et al, 2018 ; Marzorati et al, 2019b ).…”
Section: Methodsmentioning
confidence: 99%
“…The EORTC QLQ-C30 ( 40) is a quality of life measure with solid psychometric properties. This measure has been translated and validated in Italian (43,44). The EORTC QLQ-C30 consists of 30 items organized into ve areas of functioning (physical, role, emotional, cognitive, and social), nine symptom subscales/items (fatigue, nausea/vomiting, pain, dyspnea, insomnia, appetite loss, constipation, diarrhea, and nancial di culties) and a Global Health/Quality of Life subscale.…”
Section: Eortc Qlq-c30mentioning
confidence: 99%